2012
DOI: 10.1002/srin.201200112
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Related to Secondary Steel Making

Abstract: A big number of publications were collected to provide an overall picture of the modeling in secondary steelmaking. The referred papers could illustrate the general and typical approaches in modeling the process and sub-processes of steelmaking. The flow, mass transfer, and heat transfer in the reactors were briefly discussed. While modeling of slag-metal interface was summarized, the strong need for further understanding of the interface was emphasized. Modeling approaches of inclusion generation, growth, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 124 publications
(166 reference statements)
0
21
0
Order By: Relevance
“…(12)(13)(14)(15)). While ladle stirring is critical for the kinetics of the metal-slag reactions, it is well established that judicious control must be exercised to avoid reoxidation and slag entrainment (11,16). For steel processed in LF under ideal conditions of agitation and with due care to prevent reoxidation, it has been observed that the final composition is very close to equilibrium (e.g.…”
Section: Deoxidation Thermodynamics and Kineticsmentioning
confidence: 99%
“…(12)(13)(14)(15)). While ladle stirring is critical for the kinetics of the metal-slag reactions, it is well established that judicious control must be exercised to avoid reoxidation and slag entrainment (11,16). For steel processed in LF under ideal conditions of agitation and with due care to prevent reoxidation, it has been observed that the final composition is very close to equilibrium (e.g.…”
Section: Deoxidation Thermodynamics and Kineticsmentioning
confidence: 99%
“…Gas injection can increase the homogenization of temperature and alloy elements. In addition, rising bubbles can also enhance the removal of inclusions and impurity elements such as H and N during ladle, tundish and continuous casting processes . Herein, in the industrial ladle process, there are mainly three types of plugs, namely, the hybrid plug, slot plug and porous plug to inject argon bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rising bubbles can also enhance the removal of inclusions and impurity elements such as H and N during ladle, tundish and continuous casting processes. [1][2][3][4] Herein, in the industrial ladle process, there are mainly three types of plugs, namely, the hybrid plug, slot plug and porous plug to inject argon bubbles. Different types of plugs generate various kinds of bubble distributions.…”
Section: Introductionmentioning
confidence: 99%
“…In ladle metallurgy, the mixing pattern has a large influence on the alloying time. Moreover, the inclusion removal and chemical reactions are also closely related to the flow distribution [1,2]. In order to optimize the process, argon bubbling is widely used to enhance the stirring conditions.…”
Section: Introductionmentioning
confidence: 99%